Hydrogeochemical processes controlling the salinity of surface water and groundwater in an inland saline-alkali wetland in western Jilin, China - Cui, Geng; Liu, Yan; Tong, Shouzheng (Frontiers in Ecology and Evolution, 2022)
Understanding the hydrochemical evolutionary mechanisms of surface water and groundwater in saline-alkali wetlands in arid and semi-arid regions is necessary for assessing how wetland water resource utilization and restoration processes may affect the natural interface between wetland salinity and water. The Momoge National Nature Reserve (MNNR) is an inland wetland in northeastern China that is mainly fed by irrigation water and floods from the Nenjiang River. The purpose of the present study is to describe the spatial distribution characteristics of surface water and groundwater hydrochemistry and salinity in the MNNR and analyze the main processes controlling these parameters. The composition of stable isotopes (δ2H and δ18O) and water chemistry, including the levels of Na, K, Ca, Mg, HCO3, SO4, and Cl, of 156 water samples were analyzed. The results show that the lake water in the MNNR is at a risk of salinization owing to a high degree of evaporation. The analysis of the ion ratio and mineral saturation index showed that the ions in water are primarily derived from aquifer leaching, and the precipitation of Ca2+ and Mg2+ resulted in lower Ca2+ and Mg2+ levels in lake water than in groundwater. Hydrogen and oxygen stable isotope and deuterium excess analyses show that evaporation is the dominant factor controlling the hydrochemistry and salinity of lake water in the MNNR. Long-term effective monitoring of lake water and groundwater must be developed to provide an early warning for the salinization of lake water and a scientific basis for the protection and restoration of wetland ecosystem functions within the MNNR.